Protective effects of luteolin on cognitive impairments induced by psychological stress in mice. (April 2013) - Liu, Yi; Gou, Ling-Shan; Tian, Xia; Fu, Xiao-Bin; Ling, Xin; Sun, Ling-Yan; Lan, Nuo; Li, Sai; Yin, Xiao-Xing
In the present study, the protective effects of luteolin were investigated against psychological stress-induced cognitive impairment. To emulate the psychological stress, mice received restraint stress for six hours daily, between 9:00 and 15:00 hours, for 21 consecutive days. The results of step-through test, open-field test and Morris Water Maze test demonstrated that psychological stress treatment could result in cognitive impairments in mice. This cognition dysfunction was improved by treatment with low- and medium-dose luteolin. In addition, psychological stress induced an increased serum corticosterone concentration with a decreased serum norepinephrine and dopamine concentration. These alterations were attenuated by treatment with luteolin. Also, psychological stress significantly decreased the glutathione (GSH) concentrations and superoxide dismutase (SOD) activities in prefrontal cortex and hippocampus, while the malondialdehyde (MDA) concentrations were enhanced. However, these oxidative alterations in prefrontal cortex and hippocampus induced by psychological stress were significantly reversed by treatment of luteolin. Further, the current study indicated a decline of catalase (CAT) activities in the hippocampus of the ST group, which was significantly prevented by low, medium and high dose of luteolin. On the other hand, there was no significance in CAT activities of the prefrontal cortex among the six groups. Collectively, the present results suggest that luteolin treatment serves as a key role in improving the psychological stress-induced cognitive impairments.